PENDIDIKAN INKLUSI DI SEKOLAH DASAR ISLAM - Fadillah, Ahmad Arif; Sulaiman, Abdul Mugni Saudi; Ayumi, Anis; Saharani, Aura Luthfia; Putri, Chika Meiliana; Nuraulia, Dhea; Aziz, Dhilla Shafirra; Najah, Mia Alfiatun; Pertiwi, Nabila Putri; Rizki, Nabilla Oktaviani; Kamilatun, Nur Ahya; Fadiniyah, Qiromah (Transpublika Publisher, 2022)
Education is a major milestone in supporting a person's success and success, which is obtained from early childhood until the person enters adolescence or adulthood. Inclusion education is an educational service that arranges for students who have disabilities, special needs or disabilities to be served at school together with their peers, without having to be assigned classes, where the student can carry out teaching and learning activities with other children normally with adequate accessibility. The application of inclusive education in Islamic elementary schools has a positive influence on children who have disabilities or special needs, so that they get the opportunity to be able to enjoy learning activities in schools as well as other children, where they are also a priority that must be considered without being discriminated against. This study discusses the role or importance of inclusion education applied in Islamic elementary schools. The results showed that inclusive education can be said to be effective and beneficial for children who have a special need or disability for the implementation of their rights in obtaining a fair and decent education so that they can become successful individuals in the future.